Knowledge production practices in higher institutions of learning in Zambia: a case of the University of Zambia - Kanyengo, Christine Wamunyima (University of Cape Town, 2021)
The core business of higher education institutions such as universities is knowledge production. This is achieved by conducting research which results in various research products being produced, as well as through teaching and the production of graduates. The main objective of the study was to explore and describe knowledge production practices and their attributes within a university environment at the University of Zambia. The study's major contribution to knowledge is that it indicates to what extent this objective is achieved. A mixed methods case study approach that used both quantitative and qualitative research methodology was adopted for the study. The mixed methods analysis framework was based on grounded theory, bibliometric techniques, and concurrent triangulation. The site of investigation was the School of Medicine at the University of Zambia. The sampling technique also adopted a mixed methods approach by using purposive, availability and stratified purposeful sampling to sample the respondents. The PubMed/Medline database, academic staff, key informants and the documents reviewed all served as the key sources of information for the study. Data obtained from PubMed/Medline, questionnaires and semi structured interviews were quantitatively analysed using the Statistical Package for the Social Sciences (SPSS) software, while the more qualitative information that was gleaned from open-ended questions, semi-structured interviews and documentary sources was analysed thematically. The subject analysis of PubMed/Medline articles was done using the VOSviewer software and Microsoft Excel. The findings reveal that the yearly research output from 1995 to 2015 was 281 scholarly papers in 159 journals. The lowest number of papers published were recorded in 1997, 2000, and 2004 while the years 2013, 2014 and 2015 show the highest number of papers per year; and the highest was recorded in 2015. It was found that, except in 1997 and 2000, most of these papers were authored by more than five researchers. This indicates a high degree of collaboration. The journals in which the academic staff were publishing in emanated from all over the world; Asia, Africa, Europe and North America. The journals themselves are also a combination of both high impact factor journals such as the PLoS One, American Journal of Tropical Medicine and Hygiene, International Journal of Tuberculosis and Lung Disease, The Lancet, Malaria Journal and those with no impact factor like the Medical Journal of Zambia. The results indicate that the respondents mostly investigated and published in subject fields related to diseases most prevalent in Zambia, i.e. HIV and Aids, Malaria and Tuberculosis. In addition, the findings indicate that the majority of the academic staff were born after 1960 (73%), with high digital information retrieval skills (95.2%), and with their research output published mainly in journals. The knowledge was produced for various reasons: 85.4% for research purposes, 80.5% for academic promotion, 80.5% for production of knowledge, 73.2% to improve teaching, 61% to provide evidence, 51.2% to change practice, 41.5% to improve policy, 41.5% for personal advancement, and 24.4% for research funding. The knowledge was produced ethically, advancing scholarship, and deemed to be beneficial to society. The overall conclusion drawn from the study is that the knowledge productivity of the School of Medicine has steadily increased over the years and that this is supported by various institutional policies. Additionally, there is increased collaboration with persons outside the continent, whilst there is less collaboration with countries in Africa. The key recommendation for the School of Medicine is that it should work with and within the various layers of the university's institutions such as the Library, Directorate of Research and Graduate Studies, University of Zambia Press, and the Centre for Information and Communication Technology. This would ensure that impediments to knowledge production, diffusion and utilisation are mitigated.